Neuroleptic malignant syndrome - Mariana Moscovich; Felipe T.M. Nóvak; Artur F. Fernandes; Tatiana Bruch; Tabita Tomelin; Edison M. Nóvak; Renato P. Munhoz; Hélio A.G. Teive (Arquivos de Neuro-Psiquiatria)
Neuroleptic malignant syndrome (NMS) is a potentially fatal adverse event associated with the use of antipsychotics (AP). The objective of this study was to investigate the profile of cases of NMS and to compare our findings with those published in similar settings. A series of 18 consecutive patients with an established diagnosis of NMS was analyzed, gathering data on demography, symptoms and signs. Two thirds of all cases involved woman with a past medical history of psychiatric disorder receiving relatively high doses of AP. The signs and symptoms of NMS episodes were similar to those reported in other series and only one case had a fatal outcome, the remaining presenting complete recovery. As expected, more than two thirds of our cases were using classic AP (68%), however the clinical profile of these in comparison with those taking newer agent was similar. Newer AP also carry the potential for NMS.